KONTRIBUSI KELENTUKAN, KESEIMBANGAN DAN AKURASI PASSING TERHADAP KETERAMPILAN DASAR BERMAIN SEPAKTAKRAW MAHASISWA PRODI PENJASKESREK UNIVERSITAS ISLAM INDRAGIRI - Dahrial Dahrial (FKIP Universitas Islam Indragiri, 2018)
Abstrac: Based on the research in the field, basic of playing sepaktakraw still low from lecturer’s expected. The purpose of this researchs are (1) the contribution of flexibility on basic skill in playing sepaktakraw (2) the contribution of dynamic balance on basic skill in playing sepaktakraw (3) the contribution of accuracy passing on basic skill in playing sepaktakraw (4) the contribution of flexibility, dynamic balance, accurate passing throughout on basic skill in playing sepaktakraw. This is a quantitative research, the population of this researchs are 20 male students in university Islamic of Indragiri. The sampling jenuh, the researcher gets 20 students as a sample. The instrument of this research used sit and reach test for flexibility, and dynamic balance test for balancing, an accuracy passing test for accuracy passing in playing sepaktakraw, and instrument test for sepaktakraw skill. To analysis the data, the researcher used simple correlation and multiple correlation. The result of analysis the data showed (1) the result of contribution of flexibility on basic skill in playing sepaktaktaw University Islamic of Indragiri is 15.21% (2) the result of contribution of dynamic balance on basic skill in playing sepaktakraw University Islamic of Indragiri is 27.04% (3) the result of accuracy passing on basic skill in playing sepaktakraw in University Islamic of Indragiri is 26.01 % (4) there is significant contribution among flexibility, dynamic balance in playing sepaktakraw for students penjaskesrek sport faculty University Islamic of Indragiri with contribution is 47.61%.